2018
DOI: 10.1016/j.lwt.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Survey of mycotoxins in beer and exposure assessment through the consumption of commercially available beer in Lleida, Spain

Abstract: A multianalyte method, using a MS/MS detector, was applied for a simultaneous determination of 23 mycotoxins in 64 beer products purchased from the supermarket in Lleida, Spain. The samples varied by their origin, brewing technology, alcohol content, etc. The results showed that 20.3% of the tested samples were mycotoxin contaminated overpassing the limit of detection (LOD). None of the alcohol-free samples (17%) were contaminated with mycotoxins. The most frequently occurring toxin was zearalenone (ZEN), bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
4
17
1
Order By: Relevance
“…There are limited surveys that classify samples for data analysis (Rodriguez Carrasco et al 2015;Peters et al 2017;Pascari et al 2018a). In our study, beers with an alcohol content greater than 5.5 % had mycotoxin contamination in 60 % of the samples analyzed, similar to the results reported by Pascari et al (2018b).…”
Section: Estimation Of Mycotoxins Daily Intake and Exposure Risksupporting
confidence: 87%
See 1 more Smart Citation
“…There are limited surveys that classify samples for data analysis (Rodriguez Carrasco et al 2015;Peters et al 2017;Pascari et al 2018a). In our study, beers with an alcohol content greater than 5.5 % had mycotoxin contamination in 60 % of the samples analyzed, similar to the results reported by Pascari et al (2018b).…”
Section: Estimation Of Mycotoxins Daily Intake and Exposure Risksupporting
confidence: 87%
“…Those are lower than the recommendation of the JEFCA (2010) of 1000 ng kg -1 bw d -1 . The percentage of TDI of DON mycotoxins that beer provides as a result of LB consumption is similar that reported by Pascari et al (2018a) in Spain (1.6 %) and lower that than obtained by Bauer et al (2016) (5-10 %) and Rodríguez-Carrasco 2015 (10 %) in beer consumers from Germany and Ireland respectively. Regarding other products, TDI in the LB scenario that 14 beer provides for exposure to DON is similar to bread (5.3 ng kg -1 bw d -1 ) and cookies (5.7 ng kg -1 bw d -1 ) in the population of Brazil (Savi et al 2016) and pasta (22 ng kg -1 bw d -1 ) in Spain.…”
Section: Estimation Of the Don Intake Via Beer Consumption In Varioussupporting
confidence: 81%
“…However, differences could be observed in the prevalence of DON in beer samples. Pascari et al [33] analyzed 64 commercially available European beers but found DON only in 4 samples (6%), whereas ZEN was present in 65% of the samples they examined; with concentrations ranging between 8.24 and 62.98 ng/mL. This is in contrast to our study where ZEN was present in only 6% of the samples, and at levels below 0.5 ng/mL.…”
Section: Resultscontrasting
confidence: 99%
“…Even if the maximum detected DON concentrations are taken into account, the PDI values remain a small percentage of the TDI values, regardless of the country of origin of the beer. For example, the PDI is 14.0-20.8% of the TDI in Poland [54]; 18% of the TDI in Brazil [46]; 0.15-6.14% of the TDI in Spain, where the average consumption is just half of that in Poland [55]; 0% of the TDI in Cyprus and 10% of the TDI in Ireland [56].…”
Section: Dietary Exposure Assessmentmentioning
confidence: 99%